OBTENÇÃO DE NANOPARTÍCULAS DE POLI (ÁCIDO LÁCTICO) CONTENDO TAMOXIFENO E AVALIAÇÃO DA CITOTOXICIDADE SOBRE HEMÁCIAS E CÉLULAS TUMORAIS - ALTMEYER, CLESCILA (2014)
Tamoxifen (TAM) is a drug widely used as an adjuvant in breast cancer therapy. Despite showing high bioavailability, has high toxicity, which may be responsible for the lack of patient adherence to treatment. The present work aimed at the development of polymeric nanoparticles as controlled release form of TAM in order to reduce possible toxicity front to healthy human cells system. The nanoparticles of poly (lactic acid) (PLA) containing citrate of tamoxifen (CTAM) were developed by the method of emulsification-solvent evaporation. An optimization procedure was performed by varying the type of surfactant (polyvinyl alcohol, polysorbate 80 or poloxamer 188) and the same concentrations (1 or 2%). The choice of the best formulation was based on features of lower mean diameter and higher encapsulation efficiency (EE%). The optimized formulation was used that 1% PVA, which had the following characteristics: 155.3 ± 4.11 nm and 85.18 ± 8.11% encapsulation of CTAM. The analysis of the drugpolymer interaction have shown that the process of nanoencapsulation generated amorphization CTAM conveyed to the nanoparticles. The in vitro release study demonstrated that CTAM has biphasic and controlled release from the nanoparticles with kinetic type of the second order coefficient Korsmeyer-Peppas indicated that the release mechanism is the diffusion-type CTAM. In the cell toxicity tests erythrocytes, nanoparticles containing CTAM showed no hemolytic potential, in contrast to free drug which showed high erythrocyte lysis. When evaluated the cytotoxicity on Hela tumor cell line, CTAM nanoencapsulado had lower cytotoxic than free CTAM, but maintained antitumor drug action. The results show that the nanoparticles have a potential for application as controlled release of antitumor treatments CTAM system.